Philanthrocapitalism: Promoting Global Health but Failing Planetary Health - Colin D Butler (Challenges, 2019)
Focusing on the Bill and Melinda Gates Foundation (BMGF) as a case study, this paper explores the relationship between philanthrocapitalism, economic history, and global and planetary health. The Wellcome Trust is also briefly discussed, chiefly in the context of planetary health. The paper argues that in the last 45 years there has been an increased preference for market-based approaches, often called neoliberalism, particularly in the U.S. and its allies. This has generated greater inequality in many high-income settings and weakened the norm of taxation. This has provided a setting in which philanthrocapitalism has flourished, including the BMGF. The latter has in turn become an important actor for global health, partially balancing the adverse consequences of neoliberalism. Planetary health is here defined as the interaction between global health and global environmental change, including to the climate and other elements of the Earth System. Although the Wellcome Trust has recently made funds available for ecological health research, it continues to invest in fossil fuels. The Gates Foundation provide no or minimal grants for ecological or planetary health but appear to have recently substantially divested from fossil fuels, for unclear reasons. The paper concludes that these large philanthrocapitalist organizations partly compensate for the decline in attention to global health driven by market-preferring solutions, but remain insufficiently proactive in the face of the great dangers associated with declining planetary health.